View‐Sharing Artifact Reduction With Retrospective Compressed Sensing Reconstruction in the Context of Contrast‐Enhanced Liver MRI for Hepatocellular Carcinoma (HCC) Screening. Issue 4 (2nd November 2018) - Shaikh, Jamil; Stoddard, Paul B.; Levine, Evan G.; Roh, Albert T.; Saranathan, Manojkumar; Chang, Stephanie T.; Muelly, Michael C.; Hargreaves, Brian A.; Vasanawala, Shreyas S.; Loening, Andreas M.
Abstract : Background: View‐sharing (VS) increases spatiotemporal resolution in dynamic contrast‐enhanced (DCE) MRI by sharing high‐frequency k ‐space data across temporal phases. This temporal sharing results in respiratory motion within any phase to propagate artifacts across all shared phases. Compressed sensing (CS) eliminates the need for VS by recovering missing k ‐space data from pseudorandom undersampling, reducing temporal blurring while maintaining spatial resolution. Purpose: To evaluate a CS reconstruction algorithm on undersampled DCE‐MRI data for image quality and hepatocellular carcinoma (HCC) detection. Study Type: Retrospective. Subjects: Fifty consecutive patients undergoing MRI for HCC screening (29 males, 21 females, 52–72 years). Field Strength/Sequence: 3.0T MRI. Multiphase 3D‐SPGR T1 ‐weighted sequence undersampled in arterial phases with a complementary Poisson disc sampling pattern reconstructed with VS and CS algorithms. Assessment: VS and CS reconstructions evaluated by blinded assessments of image quality and anatomic delineation on Likert scales (1–4 and 1–5, respectively), and HCC detection by OPTN/UNOS criteria including a diagnostic confidence score (1–5). Blinded side‐by‐side reconstruction comparisons for lesion depiction and overall series preference (–3–3). Statistical Analysis: Two‐tailed Wilcoxon signed rank tests for paired nonparametric analyses with Bonferroni‐Holm multiple‐comparison corrections. McNemar's test for differences in lesion detection frequency and transplantation eligibility. Results: CS compared with VS demonstrated significantly improved contrast (mean 3.6 vs. 2.9, P  < 0.0001) and less motion artifact (mean 3.6 vs. 3.2, P  = 0.006). CS compared with VS demonstrated significantly improved delineations of liver margin (mean 4.5 vs. 3.8, P  = 0.0002), portal veins (mean 4.5 vs. 3.7, P  < 0.0001), and hepatic veins (mean 4.6 vs. 3.5, P  < 0.0001), but significantly decreased delineation of hepatic arteries (mean 3.2 vs. 3.7, P  = 0.004). No significant differences were seen in the other assessments. Data Conclusion: Applying a CS reconstruction to data acquired for a VS reconstruction significantly reduces motion artifacts in a clinical DCE protocol for HCC screening. Level of Evidence : 3 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:984–993.